2019
DOI: 10.3390/antiox8100437
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying of Blueberry Juice-Maltodextrin Mixtures: Evaluation of Processing Conditions on Content of Resveratrol

Abstract: Resveratrol is an antioxidant abundant in red fruits, and one of the most powerful inhibiting reactive oxygen species (ROS) and oxidative stress (OS) produced by human metabolism. The effect of the spray drying processing conditions of blueberry juice (BJ) and maltodextrin (MX) mixtures was studied on content and retention of resveratrol. Quantitatively, analysis of variance (ANOVA) showed that concentration of MX was the main variable influencing content of resveratrol. Response surface plots (RSP) confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In this study, we demonstrated that resveratrol can effectively inhibit cell proliferation and pro- Annexin 10 0 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 Annexin Numerous previous studies have demonstrated that resveratrol has antioxidant, anticancerogenic, and immunomodulatory properties. It is well documented that resveratrol has remarkable efficacy in inhibiting cell proliferation and promotes cell apoptosis in various tumour cells [21][22][23]. However, the role of resveratrol in regulating TNF-α-induced tumour-like growth of synovial fibroblasts and its underlying mechanisms have not been fully illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that resveratrol can effectively inhibit cell proliferation and pro- Annexin 10 0 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 10 0 10 1 10 2 10 3 10 4 Annexin Numerous previous studies have demonstrated that resveratrol has antioxidant, anticancerogenic, and immunomodulatory properties. It is well documented that resveratrol has remarkable efficacy in inhibiting cell proliferation and promotes cell apoptosis in various tumour cells [21][22][23]. However, the role of resveratrol in regulating TNF-α-induced tumour-like growth of synovial fibroblasts and its underlying mechanisms have not been fully illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Spray drying is a practical technique for food processing that promotes the conservation of antioxidants and the encapsulation of active compounds in the form of powdered products [ 12 ]. This technique has gained popularity in segments of the food industry because of the reduced packing volume, storage, and transportation costs [ 13 , 14 , 15 , 16 ]. Spray drying has been employed in the encapsulation of active compounds during the drying of vegetables and fruit juices [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical stability refers to how readily the resveratrol molecule can undergo chemical reactions that modify the hydroxyls and the carbon–carbon double bond [ 47 , 48 ]. The RP-HPLC results indicated that resveratrol degradation occurred in all prepared nanoemulsions due to the high sensitivity of the resveratrol chemical structure to thermal and oxidative stresses during the processing steps and the short-term storage at 25 °C ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The RP-HPLC results indicated that resveratrol degradation occurred in all prepared nanoemulsions due to the high sensitivity of the resveratrol chemical structure to thermal and oxidative stresses during the processing steps and the short-term storage at 25 °C ( Table 4 ). The degradation of resveratrol in nanoemulsions during processing/storage might be seriously accelerated by the large total surface area of all oil droplets as a result of a size reduction to the nanometer scale [ 48 ]. The loss of resveratrol during processing/storage has been attributed to factors such as pH, heat, light, and oxygen [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation